MOBILIZATION OF MIDWIFERY CARE FOR POSTPARTUM WOMEN AT PMB MONICA ROSWIYANTI, S.Tr.Keb - ANAFIKA, ANAFIKA (Universitas Aisyah Pringsewu, 2024)
Involution is when the uterus returns to its pre-pregnancy state weighing about 60 grams. This process begins immediately after delivery of the placenta due to contractions of the smooth muscles of the uterus. Involution is caused by continuous contraction and retraction of uterine muscle fibers. The way to reduce morbidity in the postpartum period is to carry out early mobilization to accelerate uterine involution. Early mobilization or activity as soon as possible after resting for several hours and getting out of the mother's bed. This report's purpose is to teach patients early mobilization independently according to the steps and theory trained in Basic Clinical Practice Skills. The method used in this report is a case study. This report shows that after being taught to do early mobilization, postpartum mothers can tilt, sit, and walk around. Early mobilization steps have been carried out according to the procedure. The author suggests improving the Midwifery Clinic Basic Skills that are owned to improve the care that, by standards carried out skillfully, can overcome real problems in practice and apply according to the theory obtained in lectures.